CAMPUS ANNOUNCEMENT AND INTERACTION SYSTEM (CAIS) - Chuah, Chin Yin (Universiti Malaysia Sarawak (UNIMAS), 2015)
This paper proposed an Android mobile application for the UNIMAS community. The expected result will be a mobile application to run on any Android platform devices that provides group announcement feature as well as individual communication. The selectable group can deliver messages to specific group of students or lecturers based on their involvement in each grouping. The system will allow users to send and receive notifications and messages. Besides, a local server will be set up as it plays an important role in user login authentication and account management. The server will house all users' profile information to be used for the grouping formation later by the mobile app.